2022
DOI: 10.3390/vaccines10030420
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Concerning Herpes Zoster among People with COPD: An Interventional Survey Study

Abstract: Herpes zoster (HZ) is common in older adults with conditions such as chronic obstructive pulmonary disease (COPD). Effective prevention is available through vaccination, but HZ vaccine uptake remains incomplete. Using an online survey of people with self-reported COPD, ShiPPS assessed HZ risk awareness, HZ vaccine use and barriers, and the impact of an HZ educational video on vaccine intent. USA members of the COPD Foundation’s Patient-Powered Research Network aged >50 years were surveyed in fall 2020. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Further, age was reported by more than two-thirds (78%) of the participants, and chronic diseases by more than half (58.5%) of the participants and this was found to be consistent with the findings reported in the previous study [ 22 ]. The majority (88.2%) of the participants had previously heard about the shingles vaccine and this percentage was much higher than the percentage found in the congruent study carried out by Yang Tu as only 43.6% of participants had heard about the shingles vaccine and this could be attributed to differences in the studied samples [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Further, age was reported by more than two-thirds (78%) of the participants, and chronic diseases by more than half (58.5%) of the participants and this was found to be consistent with the findings reported in the previous study [ 22 ]. The majority (88.2%) of the participants had previously heard about the shingles vaccine and this percentage was much higher than the percentage found in the congruent study carried out by Yang Tu as only 43.6% of participants had heard about the shingles vaccine and this could be attributed to differences in the studied samples [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study the main source of vaccine information is family and friends as Alkhalidi et al study and not television and Internet advertisements as Baalbaki’s ( 6 , 8 ). Yawn et al study among COPD patients showed that the main source of information was from primary care office ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Yawn study among COPD, only (27.1%) had reported in that they knew that COPD increased HZ risk. He also mentioned participant-reported rates of discussion or recommendations by an HCP for influenza and pneumococcal vaccines were substantially higher than for HZ vaccines ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the knowledge, attitudes and practices of cardiac HPs towards RZV, data were collected using a three-part self-administered questionnaire that comprised a series of questions adapted to the Italian context from the existing literature [23][24][25]. Part one of the questionnaire gathered information on HPs' demographic and professional characteristics, such as gender, age, educational level, professional role, area of work (i.e., the hospital unit), experience of managing patients with HZ and previous professional updates on vaccinations.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…However, the currently available literature has only lightly investigated the knowledge and attitudes of healthcare personnel towards RZV, and literature gaps still exist on the topic at hand [23][24][25]. In particular, nothing has been published on the knowledge, attitudes and practices of cardiac HPs on this topic, despite the greater clinical benefit of vaccinations for patients with cardiovascular conditions, as mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%